PERANAN DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN BATANGHARI DALAM PELAKSANAAN HAK MENGAJUKAN RANCANGAN PERATURAN DAERAH SETELAH ADANYA REPOSISI DAN REFUNGSIONALISASI DPRD (Studi Kasus DPRD Periode 2009-2014) - Herma Yanti (Universitas Batanghari Jambi, 2013)
The existence of repositioning and recreation of post-reform parliament has put Parliament in a position parallel to the local government, and restored to proper functioning as the regional legislature. Placed before Parliament as part of the Local Government Council is not able to play a lead role as it should. With repositioning and recreation of this, Parliament should be able to play a role in local governance, including the formation of legislation are realized through the implementation of the right to initiate draft.Keyword : Ranperda Council initiative